2017
DOI: 10.1080/14779072.2017.1348229
|View full text |Cite
|
Sign up to set email alerts
|

Remote monitoring of heart failure: benefits for therapeutic decision making

Abstract: Chronic heart failure is a cardiovascular disorder with high prevalence and incidence worldwide. The course of heart failure is characterized by periods of stability and instability. Decompensation of heart failure is associated with frequent and prolonged hospitalizations and it worsens the prognosis for the disease and increases cardiovascular mortality among affected patients. It is therefore important to monitor these patients carefully to reveal changes in their condition. Remote monitoring has been desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 114 publications
0
20
0
Order By: Relevance
“…These devices use various technologies, including bioimpedance, wireless pulmonary artery pressure monitors, and dielectric sensing. These devices have shown to reduce the incidence of HF mortality and inpatient admissions and represent a useful tool in tracking HF patients 22,23. In this context, to be effective, monitoring must also be complemented with effective OP management strategies in the event that disease progression cannot be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…These devices use various technologies, including bioimpedance, wireless pulmonary artery pressure monitors, and dielectric sensing. These devices have shown to reduce the incidence of HF mortality and inpatient admissions and represent a useful tool in tracking HF patients 22,23. In this context, to be effective, monitoring must also be complemented with effective OP management strategies in the event that disease progression cannot be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Progression in non-invasive digital technologies have renewed potential for remote-monitoring solutions [8,9]. Wearable sensors offer an opportunity for sensoralerting systems to continuously monitor vital parameters remotely, recognise early deterioration and support clinical decision making, allowing people to receive monitoring outside of expensive hospital facilities, in resource-limited hospitals, and utilising alternate sites in crisis scenarios [10].…”
Section: Introductionmentioning
confidence: 99%
“…Wearable sensors offer an opportunity for sensor alerting systems to continuously monitor vital parameters remotely, recognise early deterioration and support clinical decision making, allowing people to receive monitoring outside of expensive hospital facilities; in resource limited hospitals; and utilising alternate sites in crisis scenarios. 8 Previous studies have demonstrated acceptability and practicability of continuous monitoring using wearable sensors on general surgical and medical wards in the UK and The Netherlands. 9,10 Initial work by Downey et al were limited by imbalanced randomisation leading to signi cant baseline differences across the two trial arms and failure to adjust for these in their analyses.…”
Section: Introductionmentioning
confidence: 99%